Educação musical em escolas / turmas multisseriadas no campo: uma pesquisa-ação - Mendes, Josefa Eliane Ribeiro (2019)
In rural education, the biggest challenge is ensuring access to education for more isolated populations. In many rural schools, the whole school organization is adjusted into multigrade classes, which are characterized by bringing together, in the same physical space, students from different levels of learning (year, grade, cycle, etc.). These classes are managed by the same teacher, differing from the curriculum usually adopted. This thesis examines the characteristics of multigrade classes with the central objective of understanding and analyzing of the musical teaching and learning processes appropriate to work in this context. Specifically, it aims to: a) Characterize the education proposals of/in the rural area and the mechanisms of its operationalization in the researched municipality; b) Characterize the pedagogical practice in schools with multigrade classes; c) Discuss the relationships between the theory of the community of practice, community of music practice and the characteristics of multigrade classes; d) Verify, in a diagnostic stage, how the pedagogical-musical activities were developed in the researched schools and with what functions; e) Develop a pedagogical-musical process in multigrade classes of elementary school I, aiming at a constant interaction with the students' musical experience; f) Promote the involvement, participation and development of students and teachers during the classes and throughout the process; g) Analyze the process developed during the pedagogical intervention, in its contributions and limits; h) Discuss alternatives for the process of teaching and learning music in multigrade classes; For this purpose, a documentary research was initially carried out from official MEC documents, aiming to discuss public policies, legal and normative frameworks for education in rural areas, and a bibliographic research in order to verify the state of the art for this theme. In multigrade classes no study was found on musical educational practices, which indicates the relevance of this research. An action research was then developed with students from multi-grade grades of the early childhood education and the first stage of elementary school, also seeking to involve the teachers who worked in these classes. The pedagogical intervention, which involved the researcher's role as a teacher of music education, was divided into two stages, the first being held in two municipal schools in 2017, and the second in 2018, with a multigrade class from one of these schools. In class, contemporary guidelines for music education were put into practice, with the aim of adapting them to the characteristics of age diversity and school years of multi-grade classes and their interactive character. Specifically in the second stage, the planning sought to favor the development of musical learning in communities of practice, according to the theory of Etienne Wenger. In addition, semi-structured interviews were conducted with agents involved in the research: directors, supervisors, teachers, among others. A detailed analysis and description of all stages of the intervention was made, seeking to discuss which guidelines could guide the musical teaching and learning processes in multigrade rural school classes. The results showed that, despite the difficulties, the multigrade classes are still a strong reality throughout Brazil, specifically in the Northeast. It was possible to develop a musical work in this context, built from the interests of the students, the mutual collaboration between those involved, thus making the learning more meaningful. Based on this musical practice, some guidelines have been established for the teaching of music in the context of multigrade classes.